School Leaders’ Ethnographic Reflections: Lessons for Bridging Through the Post-Pandemic Era - Caño, Sheena Aguilar; Lamela, Renee; Alcantara, Jessica M. (Future Science / FSH-PH Publications, 2023)
In the context of the evolving educational landscape, school leaders hold a pivotal position in ensuring quality education in the post-pandemic. To explore this phenomenon, the researcher employed ethnographic method and thematic analysis to interpret the reflections of secondary school leaders in Masbate province. Key themes and cultural patterns emerged from the data analysis. Along with curriculum and learning, the key theme is the implementation of diverse learning modalities and strategies to address the challenges brought by the pandemic. Health protocols and guidelines were observed. Adaptability within the education sector aligns with the values of Filipino. Further, leadership and governance, such as leadership practices that encompass modeling behavior, investing in teacher potential, and supporting teachers’ initiatives and collaboration, are the cultural patterns. Moreover, continuous improvement highlights the significance of ongoing projects, particularly those who struggle with literacy and numeracy. Passion for crafting projects, data analysis, and technology in forming project designs and enhancing students’ performance is also needed. The strong commitment came out as a cultural pattern. Lastly, with managing resources, prioritize resources for the teaching and learning process, provide opportunities for professional development, allocate financial resources to priority areas, and manage human resources equitably. Flexibility in adapting to changing circumstances while emphasizing accountability and transparency. Hence, a resilient-collaborative leadership model was crafted to support the existing situation of education in the post-pandemic. However, further studies are encouraged about this phenomenon.